THE RELATIONSHIP BETWEEN NEEDS FOR DOMINANCE WITH INTENSITY ORGANIZING STUDENT IN FACULTY DA’WAH INSTITUTION (LDF) ALMUDARRIS FKIP AT SYIAH KUALA UNIVERSITY - Wahyuni Wahyuni; Dahliana Abdullah; Abu Bakar (JIMBK: Jurnal Ilmiah Mahasiswa Bimbingan & Konseling, 2016)
The study entitled "The Relationship Between Needs For Dominance with intensity Organizing student in faculty da’wah institution (LDF) Almudarris FKIP At Syiah Kuala University" aimed to describe about  the needs for dominance with the intensity of association and relationship needs for dominance with the intensity of the association. The populations in this study were 154 people. The researcher used total population sampling technique. This study was a quantitative study with descriptive and correlational. The data collection that was used by researcher using distributing instrument in the form of scale. Those items were favorable and unfavorable, they were responded by study participants in five large-scale response. The results of the analysis of research data showed that the needs for dominance in more than half the students at the high category (58%), a small portion in middle category (32%), and a few was in the category of very high (10%). While the intensity of the association for more than half were in the high category (51%), a small portion was in the category of very high (30%), and a few are in the medium category (18%). The results of data analysis using product moment correlation test showed that the correlation between the needs for dominance with the intensity of a student association with r (xy) = 0.355 with a significant level of p 0.05 (0.210 0.05). Thus the alternative hypothesis was accepted, it meant there was a significant correlation between the needs for dominance with the intensity of the student organization, the positive correlation value indicated the higher and better the student needs for dominance tended to be higher and better organize student intensity. It could be concluded that there was a relationship between the needs for dominance with the intensity of the student organization at the faculty da’wah institution (LDF) Almudarris FKIP at Syiah Kuala University. Keywords: needs for dominance, intensity Organizing